High intake of dietary fibre from fruit and vegetables reduces the risk of hospitalisation for diverticular disease - Mahmood, Mahmood W. (Eur J Nutr, 2018)
BACKGROUNDS AND AIMS: High intake of dietary fibres has been associated with a reduced risk of DD. However, reports on which type of dietary fibre intake that is most beneficial have been conflicting. The aim of this study was to investigate the association between different dietary fibres and hospitalisation due to diverticular disease (DD) of the colon. METHODS: This was a major cohort study. The Swedish Mammography Cohort and the Cohort of Swedish Men were linked to the Swedish Inpatient Register and the Causes of Death Register. Data on the intake of dietary fibre were collected through questionnaires. The effect of intake (in quartiles) of different types of dietary fibre on the incidence of hospitalisation due to DD was investigated using multivariable Cox regression. Estimates were adjusted according to age, BMI, physical activity, co-morbidity, intake of corticosteroids, smoking, alcohol intake and education level. RESULTS: Women with intake of fruit and vegetable fibres in the highest quartile (median 12.6 g/day) had a 30% decreased risk of hospitalisation compared to those with the lowest intake (4.1 g/day). Men within the highest quartile (10.3 g/day) had a 32% decreased risk compared to those with a low intake (2.9 g/day). High intake of fibres from cereals did not affect the risk. CONCLUSION: A high intake of fruits and vegetables may reduce the risk of hospitalisation due to DD. Intake of cereals did not influence the risk.